Building human resilience: The role of community based training and awareness programme (CBTAP) for dam related flood risk management - Yahya N.; Thiruchelvam S.; Ghazali A.; Muda R.S.; Mat Isa A.A.; Jin N.Y.; Norkhairi F.F.; Hakimie H.; Kadir A.K.; Mohamed Sahari K.S.; Hasini H.; Mustapha K.N.; et al. (Akademi Sains Malaysia, 2023)
The structural elements of dams are prone to defects and potential failures despite continuous upgrade on design, variety of construction materials used, daily operation and maintenance efforts of dams to improve the safety of the dams, the possibility of unforeseen events of dam failures is still possible. Dams in Malaysia are observed to integrate community in which socio-economical activities are carried out within its vicinity. Hence, severe loss of properties and most critically, human lives might bring about should dam failures occur. It is apparent that an emergency response system should be built to reduce any loss of properties or lives as well as utilising the resources within the community. A community engagement programme is designed to guide the people about the possible threat and emergency response action aligning with the protocol or guidelines set by the dam management teams and its stakeholders. The preparedness of the community and their familiarity with the dam disaster evacuation response system could ensure higher possibilities of effective evacuation, hence minimising further losses. This paper presents such community engagement programme conducted for residents in Cameron Highlands, Kuala Berang, Kampong Gajah and Kuala Kangsar. Programme activities organised since 2015 include briefings on disaster awareness, workshops with key community leaders, and evacuation drills. Through these activities, we aimed to educate the residents in these towns, who are vulnerable to flood resulting from dam failure, to be more prepared and resilient to disasters. 2018 Akademi Sains Malaysia.